2016
DOI: 10.1016/j.foreco.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Estimating local spread of recently established emerald ash borer, Agrilus planipennis, infestations and the potential to influence it with a systemic insecticide and girdled ash trees

Abstract: Estimating local spread of recently established emerald ash borer, Agrilus planipennis, infestations and the potential to influence it with a systemic insecticide and girdled ash trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…This speed is within the range of observed speeds between 0.4–0.7 km/yr in small infestations and 1.2–1.7 km/yr in larger infestations (Mercader et al. ). Over large scales, EAB has spread much faster, but this spread was almost certainly vectored by human transportation, which is not the focus of our work.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This speed is within the range of observed speeds between 0.4–0.7 km/yr in small infestations and 1.2–1.7 km/yr in larger infestations (Mercader et al. ). Over large scales, EAB has spread much faster, but this spread was almost certainly vectored by human transportation, which is not the focus of our work.…”
Section: Resultssupporting
confidence: 81%
“…In a homogeneously good landscape with the Laplace kernel to describe egg distribution, the population pulse travels at a speed of c h = 0.82 km/yr and the phloem density retreats at the same rate. This speed is within the range of observed speeds between 0.4-0.7 km/yr in small infestations and 1.2-1.7 km/yr in larger infestations (Mercader et al 2016). Over large scales, EAB has spread much faster,…”
Section: Resultssupporting
confidence: 75%
“…In a recent 4-yr project encompassing 390 km 2 in northern Michigan, systematic grids of 444 to 855 small (10 to 20 cm dbh) girdled ash detection trees were deployed annually. Data acquired by debarking the girdled trees provided forest and city managers, regulatory officials and outreach specialists with extensive information on emerald ash borer distribution, density and spread across the landscape Mercader et al 2015Mercader et al , 2016. The debarked trees also functioned as population sinks, resulting in detectable effects on local emerald ash borer population growth (Mercader et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Model results indicated that emerald ash borer spread rates were reduced from areas with girdled trees. Trees treated with the systemic insecticide also reduced larval abundance in subsequent years (Mercader et al 2015(Mercader et al , 2016. The Pennsylvania Department of Agriculture has developed and implemented a pest management strategy to suppress the spotted lanternfly population focusing on the core of the infested area and working outward using the trap tree/host removal method as well as pesticide applications.…”
Section: Integrated Pest Management Programsmentioning
confidence: 99%